The carbon footprint of business travel in the knowledge-intensive service sector. (January 2017) - Poom, Age; Orru, Kati; Ahas, Rein
Highlights: Co-production of new knowledge in business communication benefit from physical proximity. Strong interpersonal ties allow physical co-presence to be substituted by virtual communication. Trips related to core business processes cause the highest carbon footprint. Marketing is the most vulnerable business phase due to its high requirement of co-presence. Low-carbon communication and travel modes should be considered in business travel management. Abstract: We explore the travel needs and patterns, and the corresponding carbon footprint, of small service organizations during different phases of knowledge-intensive business processes, and compare the results with the priorities given to travel-related goals by staff. We apply a combination of focus group data, mobile positioning, and individual follow-up interviews as study methods. The need for physical travel is determined by a combination of the perceived potential for knowledge creation and transfer offered by each trip, the strength of interpersonal relationships in business networks, and the significance of the travel goal in terms of economic sustainability. The priorities given to travel goals reflect the environmental load of business travel only in domestic contexts, where executing core business processes accounted for the highest carbon footprint. We propose the ways in which the management of business interactions could take into account sociotechnical environment and social recognition of low-carbon communication and travel modes.